Implementasi Kegiatan Ekstrakulikuler dalam Membentuk Karakter Religius Siswa di SMPN 04 Bantan - Misran, M; Robiah (STAIN Bengkalis, 2024)
This study discusses extracurricular activities at SMPN 04 Bantan, focusing on religious extracurricular activities in shaping students' religious character. This extracurricular activity can also hone students' abilities according to their interests, not only in academic fields but also in non-academic fields. The researcher focuses on the religious field, namely rohis. The purpose of this study is to determine the implementation of extracurricular activities in shaping students' character, supporting factors, and to determine the inhibiting factors in the implementation of extracurricular activities in shaping students' character. This study uses a qualitative descriptive method with research instruments in the form of observation guidelines, interviews, and documentation. Data processing and analysis used in this study include data collection, data reduction, data presentation, and drawing conclusions. The results of the study regarding the implementation of extracurricular activities at SMPN 04 Bantan are quite good. This activity is supported by the principal and is well scheduled by the vice principal for curriculum. Supporting factors for extracurricular activities at SMPN 04 Bantan include the cohesiveness of teachers at school and the enthusiasm and discipline of students in carrying them out. However, there are several inhibiting factors, such as inadequate infrastructure, for example a small prayer room so that prayers have to be performed in turns. Penelitian ini membahas tentang ekstrakurikuler di SMPN 04 Bantan, dengan fokus pada ekstrakurikuler keagamaan rohis dalam membentuk karakter religius siswa. Ekstrakurikuler ini juga dapat mengasah kemampuan siswa sesuai dengan minat mereka, tidak hanya dalam bidang akademik tetapi juga dalam bidang non-akademik. Peneliti memfokuskan pada bidang keagamaan, yaitu rohis. Adapun tujuan penelitian ini adalah untuk mengetahui implementasi kegiatan ekstrakurikuler dalam membentuk karakter siswa, faktor pendukung, serta mengetahui faktor penghambat implementasi kegiatan ekstrakurikuler dalam membentuk karakter siswa. Penelitian ini menggunakan metode deskriptif kualitatif dengan instrumen penelitian berupa pedoman observasi, wawancara, dan dokumentasi. Pengolahan dan analisis data yang digunakan dalam penelitian ini meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian mengenai implementasi kegiatan ekstrakurikuler di SMPN 04 Bantan terbilang cukup baik. Kegiatan ini didukung oleh kepala sekolah dan terjadwal dengan baik oleh wakil kepala sekolah bidang kurikulum. Faktor pendukung ekstrakurikuler di SMPN 04 Bantan antara lain adalah kekompakan guru-guru di sekolah serta antusiasme dan kedisiplinan siswa dalam menjalankannya. Namun, terdapat beberapa faktor penghambat, seperti prasarana yang kurang memadai, contohnya musholla yang kecil sehingga harus dilakukan sholat bergiliran.